2010
DOI: 10.1128/cvi.00235-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Orthopoxvirus Type I Interferon-Binding Molecule as a Vaccine Target in the Vaccinia Virus Intranasal Murine Challenge Model

Abstract: The biological threat imposed by orthopoxviruses warrants the development of safe and effective vaccines. We developed a candidate orthopoxvirus DNA-based vaccine, termed 4pox, which targets four viral structural components, A33, B5, A27, and L1. While this vaccine protects mice and nonhuman primates from lethal infections, we are interested in further enhancing its potency. One approach to enhance potency is to include additional orthopoxvirus immunogens. Here, we investigated whether vaccination with the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our mutagenesis studies of the residues involved in GAG binding indicate that the amino-terminal part of the IFN␣/␤BP is crucial for its cell-binding ability. Experimental evidence for the involvement of the amino-terminal region in cell binding has also been described recently (49). These results are consistent with previous studies with the VACV strain Wyeth, which encodes a truncated IFN␣/␤BP lacking the third Ig domain that retains the ability to attach to the cell surface but has lost some affinity for IFN (18).…”
Section: Discussionsupporting
confidence: 90%
“…Our mutagenesis studies of the residues involved in GAG binding indicate that the amino-terminal part of the IFN␣/␤BP is crucial for its cell-binding ability. Experimental evidence for the involvement of the amino-terminal region in cell binding has also been described recently (49). These results are consistent with previous studies with the VACV strain Wyeth, which encodes a truncated IFN␣/␤BP lacking the third Ig domain that retains the ability to attach to the cell surface but has lost some affinity for IFN (18).…”
Section: Discussionsupporting
confidence: 90%
“…Examination of a truncated version of B18 expressed by the attenuated Wyeth VACCV strain lacking its third, C-terminal immunoglobulin (Ig) domain showed that cell binding capacity is mediated by the N-terminal regions of the protein [ 221 ]. Additional transfection analyses with different constructs suggested that cell binding activity is mediated by Ig domain 1, while IFN blocking activity requires Ig domains 2 and 3 [ 223 ] Site directed mutagenesis assays identified stretches of basic residues at the N terminus of B18 to mediate high affinity binding to cell surface sulfated glycosaminoglycans, preferentially heparan sulfate [ 224 ] and showed that mutants lacking GAG binding activity could still bind and inhibit IFN efficiently.…”
Section: Viral Evasion Strategies: Secreted Ifn Binding Proteinsmentioning
confidence: 99%
“…An alternative approach for the development of safer yet efficacious vaccines is to avoid the use of live-virus-based vaccines entirely and instead identify specific subunits or epitopes from Orthopoxvirus species that confer protection and vaccinate with those subunits. Protein- and gene-based subunit vaccines against orthopoxviruses have been investigated by a number of groups [ 18 - 39 , 41 - 44 ]; for review see [ 45 ]. Our laboratory has focused on gene-based vaccines involving a combination of two MV and two EV targets.…”
Section: Introductionmentioning
confidence: 99%